Understanding the Role of Cooperatives in Economic Development - Joshi, Janak Raj (AMC Journal (Dhangadhi), 2024)
Cooperatives have played a significant role in promoting economic development across the world. This research paper aims to examine the impact of cooperatives on economic growth, including poverty alleviation, job creation, and entrepreneurship. The study employs a cross-sectional quantitative analysis of panel data on 300 cooperatives over 10 years. The dataset includes variables such as sales, employment, productivity, and exports. The research utilizes panel data regression models to test the hypotheses based on economic theories and past empirical evidence. The findings suggest that cooperatives have a positive and significant impact on economic development, particularly in terms of reducing poverty, generating employment opportunities, and fostering entrepreneurship. The paper concludes with implications for theory and policymaking, as well as limitations and suggestions for further research.